2010
DOI: 10.1111/j.1365-3121.2010.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Raman spectrum of carbonaceous material in low-grade metasediments of the Glarus Alps (Switzerland)

Abstract: Terra Nova, 22, 354–360, 2010 Abstract The Raman spectrum of carbonaceous material (CM) from advanced diagenesis (∼200 °C) to low‐grade metamorphism (∼320 °C) is documented in the Helvetic flysch of the Glarus Alps (Switzerland). The spectrum is complex, with several defect bands at ∼1200 (D4), ∼1350 (D1), ∼1500 (D3) and ∼1620 (D2) cm−1. We document the evolution of these bands relative to the ‘graphite’ G band with increasing metamorphic grade, and we show that this qualitative evolution may be used as a prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
572
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 367 publications
(603 citation statements)
references
References 21 publications
26
572
0
5
Order By: Relevance
“…Furthermore, Marshall et al (2001Marshall et al ( , 2007, and Lahfid et al (2010) demonstrated that Raman spectra acquired from CM thermally altered from 230°C to 300°C shows that the relative intensity of the D band progressively increases. Between temperatures of 300-350°C, the D band intensity is higher than the G band intensity (Marshall et al, 2001(Marshall et al, , 2007Lahfid et al, 2010). Additionally, there are several indicators that the CM in phase E1 must have been deposited before the less thermally mature CM in phase E3.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Marshall et al (2001Marshall et al ( , 2007, and Lahfid et al (2010) demonstrated that Raman spectra acquired from CM thermally altered from 230°C to 300°C shows that the relative intensity of the D band progressively increases. Between temperatures of 300-350°C, the D band intensity is higher than the G band intensity (Marshall et al, 2001(Marshall et al, , 2007Lahfid et al, 2010). Additionally, there are several indicators that the CM in phase E1 must have been deposited before the less thermally mature CM in phase E3.…”
Section: Discussionmentioning
confidence: 99%
“…The two-peak fit led to four correlations with R 2 ≥ 0.79 with VRo, and five correlations with R 2 ≥ 0.90, even though this fitting strategy did not portray every vibrational mode. The literature reflects this conundrum, as peak-fitting protocols utilizing 2 to 10 peaks have been published (Quirico et al, 2005;Guedes et al, 2010Guedes et al, , 2012Lahfid et al, 2010;Hinrichs et al, 2014;Lünsdorf et al, 2014;Wilkins et al, 2014;Li et al, 2015;Lünsdorf, 2016;Schito , 2017). While more peaks can lead to reduced χ 2 values, how many peaks accurately represent the sample?…”
Section: Discussionmentioning
confidence: 99%
“…Recent progress on the Raman microscopy utilizes carbonaceous material (CM) as a convenient in situ temperature indicator (e.g., Beyssac et al, 2002). A variety of geologic situations become available for the application of Raman spectra of carbonaceous material (RSCM) geothermometer: regional metamorphism (Beyssac et al, 2002), contact metamorphism (Aoya et al, 2010), lowgrade metamorphism down to the zeolite-facies (Rahl et al, 2005;Lahfid et al, 2010;Kouketsu et al, 2014), and even for the extraterrestrial materials whose peak metamorphic temperature is below 100°C (Homma et al, 2015). Notably, the RSCM geothermometer is applicable for low-temperature conditions (approximately <400°C) where conventional thermodynamic approaches have difficulties due to the slow rate of metamorphic reactions (i.e., chemical equilibrium is not always attained: Cho and Liou, 1987).…”
Section: Introductionmentioning
confidence: 99%